OP0236 Benefit and safety of antithrombotic treatment in 264 pregnancies in patients with antiphospholipid syndrome. (15th June 2017) - Yelnik, CM; Lambert, M; Drumez, E; Guern, V Le; Bacri, J-L; Guerra, M; Laskin, CA; Branch, W; Sammaritano, LR; Morel, N; Guettrot-Imbert, G; Launay, D; et al.
Abstract : Background: The management of pregnancy in patients with antiphospholipid syndrome (APS) with aspirin and heparin is based on empiric recommendations. Objectives: Our study aimed to evaluate the outcomes of treated patients with thrombotic and obstetric APS and the safety of antithrombotic treatments prescribed during pregnancy. Methods: Inclusion criteria were (1) APS (Sydney criteria), (2) live pregnancy at 12 weeks of gestation (WG) with (3) follow up data until 6 weeks post-partum. Data were collected prospectively (PROMISSE study) and retrospectively (four French centers). Adverse pregnancy outcomes (APOs) were defined by fetal death or neonatal death; pre-term delivery before 36 WG due to preeclampsia or placental insufficiency; or small for gestational-age (SGA; <5th percentile). Major bleeding was defined as blood loss greater than 500mL and/or requiring surgery or transfusion. Results: 264 pregnancies (87 collected prospectively) in 204 patients were included (46% with a history of thrombosis, and 23% with associated systemic lupus erythematosus). During pregnancy, treatment included heparin (n=253; 96%) and low-dose aspirin (n=223; 84%). The live birth rate was 86%. APOs occurred in 32%, mostly during the 2nd trimester: fetal deaths 11%, SGA 11%, pre-term delivery before 36 WG due to preeclampsia or placental insufficiency 17%. Thirteen maternal thrombotic events occurred in 12 (4.5%) pregnancies. Forty-six maternal hemorrhagic events occurred in 40 (15%) pregnancies (30 events in the post-partum period). Major bleeding was reported in only 6 pregnancies (2.3%) and occurred only after delivery. Except for two events, post-partum hemorrhage occurred in the early post-partum before hospital discharge. No maternal death was observed. Aspirin therapy during pregnancy was the only independent factor associated with a lower risk of APOs (odds ratio: 0.34; 95% CI: 0.15 – 0.78; p=0.01) in multivariate analysis. Neither heparin or aspirin alone, nor combined therapy increased the risk of hemorrhage. In the retrospective cohort, emergency caesarian section was the only factor associated with hemorrhagic events during the study period (53% hemorrhages in patients who underwent emergency caesarian compared to 18%, p=0.005). Independent risk factors for APOs were elevated body mass index and the presence of lupus anticoagulant. Conclusions: We report a high level of obstetrical complications in conventionally-treated APS pregnancies, and a beneficial effect of addition of aspirin to prevent obstetrical morbidity. Moreover, heparin and aspirin were well tolerated and did not increase risk of hemorrhage. Disclosure of Interest: None declared